United Kingdom : 2001 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the United Kingdom. (IMF Staff Country Reports; Country Report, 2002)
This 2001 Article IV Consultation highlights that in 2001, the economy of the United Kingdom grew faster than any other G-7 economy. Despite the slowdown in world demand, output grew by 2.4 percent reflecting strong domestic demand. Private consumption remained buoyant, fueled by several years of strong earnings and employment growth, low interest rates, and rising housing wealth, which largely offset the adverse impact of lower equity prices on consumer spending. Following several years of robust growth, private investment was hit by the downturn in the information and telecommunications sector.